Implementasi Sistem Informasi ERP Menggunakan Odoo dengan Modul Inventory pada PT. Seilchem Multi Persada - Junja Ramadhina; Lufty Abdillah (UNIVERSITAS KALBIS, 2026)
PT. Seilchem ​​Multi Persada is a company that sells pipe coatings with various types of coatings being sold. The problem in this company is that the stock calculation system is still manual using paper, causing inaccuracies in calculating the amount of stock. Therefore, an integrated system is needed to help with stock calculations by implementing the Odoo ERP Inventory module using the ASAP method. The purpose of this research is to make it easier for PT. Seilchem ​​Multi Persada in recording the availability of inventory in the warehouse by implementing the Odoo ERP inventory module as the main focus of research and creating a manufacturing module as a supporting module. The results of this study indicate that there is accuracy in the stock availability data after implementing the odoo system.